2012
DOI: 10.1227/neu.0b013e3182367295
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Anxiety, and Depression in Patients With an Unruptured Intracranial Aneurysm With or Without Aneurysm Occlusion

Abstract: Patients with an unruptured aneurysm have a reduced quality of life compared with the reference population, mainly in physical domains, but without an apparent effect on mood or anxiety. The extent of reduction in quality of life is similar in patients with and without aneurysm occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 9 publications
5
49
0
Order By: Relevance
“…Raaymakers et al demonstrated in a collective of 18 clipped patients a considerable negative impact on functional health and quality of life 3 months after surgery, despite a low rate of impairments, with a marked, but not complete recovery after 1 year [36]. Brilstra et al observed a similar phenomenon in a surgically treated iA patient collective, while the corresponding endovascular The standard values are representative for German females above 50 years of age life in a patient collective with untreated iA compared to a patient collective with treated iA without detecting any significant differences concerning the reduced quality-of-life scores in both groups [2,6,44]. Unfortunately, none of those studies analyzed the pre-interventional psychiatric history of the included patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Raaymakers et al demonstrated in a collective of 18 clipped patients a considerable negative impact on functional health and quality of life 3 months after surgery, despite a low rate of impairments, with a marked, but not complete recovery after 1 year [36]. Brilstra et al observed a similar phenomenon in a surgically treated iA patient collective, while the corresponding endovascular The standard values are representative for German females above 50 years of age life in a patient collective with untreated iA compared to a patient collective with treated iA without detecting any significant differences concerning the reduced quality-of-life scores in both groups [2,6,44]. Unfortunately, none of those studies analyzed the pre-interventional psychiatric history of the included patients.…”
Section: Discussionmentioning
confidence: 87%
“…Since Solheim et al were not able to detect any significant differences between the surgical and endovascular patient subgroups and patients with or without persisting neurological deficits, it was postulated that those low quality-of-life scores might be due to factors unrelated to the aneurysms or the treatment procedures themselves, but actually might reflect characteristics of a patient group likely to have incidental aneurysms diagnosed while undergoing extensive imaging procedures for unrelated symptoms [41]. Surprisingly, the quality of life did not improve after treatment of the unruptured aneurysm [6]. In contrast to those findings, it was recently demonstrated that patients with benign intracranial meningiomas have a psychiatric morbidity rate comparable to the general population after successful neurosurgical treatment [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, a response rate of 69% is comparable with other studies, and there were no major differences in baseline characteristics between participants and nonparticipants. 3,11,18 Third, patients and aneurysms treated by coiling or by surgery were incomparable, making it impossible to compare outcomes between the endovascular and microsurgical treated groups. The strength of our study is the large sample size and the use of a validated questionnaire for evaluation of life satisfaction.…”
mentioning
confidence: 99%
“…Quality of life of our patients in the long-term follow-up was similar to that of the reference Polish population, with the mean values of psychosocial domain scores even slightly higher, which could be explained by improved well-being after reducing a risk for disability or even death. Although there are reports on a decline in QoL after treatment of patients with UIA, they are attributed to fear of recurrence, which is significantly higher after endovascular coiling procedures [31,32]. Moreover, economic cost-benefit analyses from different countries have revealed that, despite a shorter length of patients' stay, the endovascular method was associated with higher hospital costs in patients with both unruptured and ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's condition was assessed using the Glasgow Outcome Scale (GOS). Next, the SF-36 was administered in order to assess the QoL, using the Polish population data as a reference [31]. A decline in QoL was determined if the direct score was one standard deviation below the mean.…”
Section: Data Collection and Analysismentioning
confidence: 99%